Ethnobotanical study of traditional medicinal plants and associated indigenous knowledge in Melokoza District, South Ethiopia - Ayele Chashike; Simon Shibru; Tizazu Gebre; Abera Uncha (Trees, Forests and People)
Preserving traditional medicinal knowledge and the community's relationship with plants is essential for environmental and health protection. This study documented traditional medicinal plants and community practices in the Melokoza from 2023 to 2024. A purposive sampling technique was employed to select sampled Kebeles. Overall, 390 respondents were identified to gather information on medicinal plants using a questionnaire survey. Preference Ranking, Fidelity Level, and Informant Consensus Factor were used to analyze the data. In general, 140 medicinal plants grouped into 115 genera of 56 families were identified in this study. Asteraceae was the most dominant family representing 19.3 % of the medicinal plants identified, followed by Lamiaceae (13.57 %). Leaves were the most commonly used part of the plants, making up 67.9 % of the plant parts used, followed by roots (10 %). Fresh plant parts were mainly used for medicine (85.71 %). Most medicinal plants were found in home gardens (27.86 %) and forest areas (22.86 %). Cold water extraction (56.92 %) was the most common method of traditional medicine preparation, followed by crushing (19.23 %). The most common way to take medicine was by drinking it in solution form. Croton macrostachyus was noted for its high preference ranking in treating wounds. The highest informant consensus factor value was recorded for stopping bleeding (0.98) and stopping vomiting (0.97) illness. The research showed that agricultural expansion is severely degrading traditional medicinal plants in Melokoza. Urgent conservation and sustainable management are needed, along with further study in the district.